Single Nucleotide Variation in the Promoter Region of the APOA1 Gene as a Candidate Biomarker for Dyslipidemia - Rahajoe, Toeti; Nugraheni, Kartika; Pinda Ayu Widiyani; Asihanto, Balqis Aureola Putri; Kartika, Aprilia Indra (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Dyslipidemia is a lipid profile abnormality that can escalate the risk of cardiovascular disease. The rate of cardiovascular events in Indonesia is very high. One of the causes of dyslipidemia is due to polymorphisms in genes associated with lipid metabolism. The APOA-1 gene encodes the APOA-1 protein which functions to regulate HDL protein synthesis. The objective of this study is to determine APOA1 gene polymorphisms in patients with dyslipidemia. Samples of healthy controls and dyslipidemia patients were used in this investigation. The lipid profiles of the patients and normal controls are determined at the onset of the study. Following DNA extraction, the APOA-1 gene was amplified and sequenced using the serum sample. MEGA X and BLAST were used to analyze the sequencing results. The study's findings demonstrated that the APOA-1 gene length in samples of dyslipidemic patients and normal controls was 433 bp. While the normal control samples have the same sequence as the database, the dyslipidemic patient samples have an APOA-1 gene polymorphism in the promoter region. APOA-1 gene polymorphism results in disturbances in lipid profiles, particularly HDL which is at risk of developing dyslipidemia. The APOA-1 gene has the potential to be developed as a biomarker for diagnosing dyslipidemia involving a larger number of samples.